Basic grammatical concepts: from theory to practice (Филологический класс, 2008)
The article focuses on the scientific approach to studying the basic notion of Linguistics - that of a grammatical category. Grammatical verb categories of person and number are defined in the article, and a number of exercises designed to analyze the categories in question are provided.